Does fiscal oversight matter? - Désirée I. Christofzik; Sebastian G. Kessing (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2018)
A gradually introduced reform of local government accounting made it temporarily possible for municipalities in the German state of North Rhine-Westphalia to avoid the effective control of their budget by the authorities in charge of overseeing local government budgets and enforcing the existing fiscal rules. Using this withdrawal of effective fiscal oversight, we identify the effects of fiscal restraints and their enforcement on fiscal outcomes. We find that the withdrawal of oversight has a significant and sizable effect on per capita debt of local governments that were previously constrained by fiscal oversight. Fiscal restraints are important, and oversight and enforcement are key requirements for their success.
Keywords: H72; H74; R50; 330; Fiscal oversight; fiscal rules; local government debt